Efficacy of Hibiscus sabdariffa L. extract on metabolic parameters in participants with abdominal obesity and mild metabolic syndrome in Bangkok, Thailand: A double-blind, randomized, placebo-controlled trial - Kanchaporn Chaisungnern; Thanapoom Rattananupong; Rossukon Klinhom; Srisuphak Nanta; Kamonwan Banchuen; Arunporn Itharat; Pranporn Kuropakornpong; Thanan Supasiri; Preecha Nootim; Wiroj Jiamjarasrangsi (Complementary Therapies in Medicine)
Background: Hibiscus sabdariffa L. (HS) has been investigated as an alternative treatment for metabolic syndrome (MetS), as it affects all MetS components with low side effects simultaneously; however, clinical evidence regarding its efficacy compared with placebo is inconsistent. This study assessed how the aqueous calyx extract of HS influences insulin resistance and MetS parameters and examined the safety effects on liver, kidney, and hematological indexes in participants with abdominal obesity and mild MetS symptoms. Methods: In this double-blind, randomized, placebo-controlled trial, 108 participants with MetS were randomly assigned to take 1000-mg HS (45.04 mg/day in total polyphenols) or placebo daily for 12 weeks. Insulin resistance (HOMA-IR), glycemic markers, body mass index (BMI), waist circumference (WC), lipid profiles, and blood pressure were assessed at baseline, 6 weeks, and 12 weeks. Additionally, liver and kidney function indicators along with hematological parameters were evaluated. Results: Compared with placebo, HS did not significantly affect HOMA-IR, glycemic markers, BMI, WC, lipid profile, or blood pressure. Although HS did not significantly alter the lipid profile overall, serum low-density lipoprotein (LDL) levels decreased significantly at 12 weeks compared with baseline (− 7.98 mg/dL, [95 % CI, − 14.80, − 1.15]). Additionally, HS did not cause significant liver or kidney function or hematological changes compared with placebo. Conclusion: Taking 1000-mg HS daily for 12 weeks seems to be safe. Placebo and HS groups showed good clinical results, and the extract was not associated with improved metabolic parameters in individuals with abdominal obesity and mild MetS symptoms, with the exception of lower serum LDL.